Impacts of Global Climate Change 2005
DOI: 10.1061/40792(173)175
|View full text |Cite
|
Sign up to set email alerts
|

Development of Adjustment and Scaling Factors for Measured Suspended Solids Removal Performance of Stormwater Hydrodynamic Treatment Devices

Abstract: Suspended solids removal performance of a manufactured stormwater treatment device varies greatly with operating conditions and laboratory or field evaluation techniques. Laboratory testing and field monitoring protocols have been established to evaluate the performance (removal efficiency or effluent concentration) of manufactured stormwater treatment devices and other structural BMPs. However, deviations from the recommended evaluation conditions and techniques are expected and may lead to a significant diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2007
2007
2009
2009

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
(6 reference statements)
0
3
1
Order By: Relevance
“…However, when a substantial portion of the solids mixture was in the sand size range, the size of the aliquot was insignificant. These results were also substantially lower than the recoveries reported by Guo and Gray et al . The “shake-and-pour” methods provided the most consistent results of the two TSS collection techniques (not dependent on aliquot collection location or aliquot size).…”
Section: Resultscontrasting
confidence: 72%
See 1 more Smart Citation
“…However, when a substantial portion of the solids mixture was in the sand size range, the size of the aliquot was insignificant. These results were also substantially lower than the recoveries reported by Guo and Gray et al . The “shake-and-pour” methods provided the most consistent results of the two TSS collection techniques (not dependent on aliquot collection location or aliquot size).…”
Section: Resultscontrasting
confidence: 72%
“…Investigations of the correlations between the SS analytical methods (3) have shown that these two methods often give varying results (4,5). All groups, including this research group, showed TSS measurements were generally lower than the SSC measurements with a TSS concentration bias ranging from 20 to 40% lower than the corresponding SSC concentration for identical samples analyzed with different methodologies.…”
Section: Introductionmentioning
confidence: 94%
“…However, the U.S. Geological Survey ͑USGS͒ in much of their water-quality monitoring efforts has used a different methodology to quantify the amount of particles in a water sample-the SSC method. They argue that TSS methods miss many of the larger solids often found in water quality samples collected in streams ͑Gray et al Guo 2005͒. A lack of understanding of the distinction between the methods also permeates some testing protocols.…”
Section: Methodsmentioning
confidence: 99%
“…Table 1-Settling distances (m) for particles flowing in pipes having various diameters and slopes (Manning's n 5 0.013; specific gravity 5 2.5; adapted from Pitt and Clark, 2006 Roesner et al, 2007). Only recently has attention been focused on quantifying the errors associated with each phase of this process, with most of the activity focusing on quantifying the concerns regarding analysis technique, including storage time and temperature and effect of PSD (Chan et al, 2008;Clark and Pitt, 2008;Siu, 2008a, 2008b;Guo, 2005Guo, , 2007Li et al, 2005;Siu et al, 2008). Earlier work by the U.S. Geological Survey (Reston, Virginia) (USGS) (Bent et al, 2001;Edwards and Glysson, 1999;Winterstein and Stefan, 1983) quantified some of the concerns regarding the ability of automatic samplers to capture solids in the different size ranges and densities that can be associated with stormwater runoff.…”
Section: Introductionmentioning
confidence: 99%